IMPLEMENTASI SINERGISITAS DARI BERBAGAI STAKEHOLDER DALAM PENGEMBANGAN DESA CINANDANG DAWARBLANDONG - Rendi Adi Pratama, Nugroho; Wijaya, Dian; Rinayuhani, Tri Ratna (Universitas Islam Majapahit, Indonesia, 2024)
Village development is a process that involves various parties to improve the quality of life of the community through the development of physical, social, economic, and environmental infrastructure. Synergy is needed to achieve common goals, with collaboration producing greater effects. Although it offers benefits, there are challenges that must be faced, but in Cinandang Village, Dawarblandong District, the implementation of synergy between the village government and the community is very significant. In village development, it is important to involve all elements of society, including women's groups, youth, and the elderly. The qualitative descriptive approach is a research method often used in the social sciences and humanities, focusing on understanding social phenomena through the collection of data that is not quantitatively measurable. This method aims to describe and understand certain phenomena through the subjective views of participants using data collection techniques such as in-depth interviews, observations, and document analysis. For example, in a partnership, one party may focus more on short-term profits, while the other is more concerned with long-term sustainability. In addition, ineffective communication can also hinder the achievement of synergy